The ST2 diagnostic value in selection of patients for heart transplantation and post-transplant period - Nikonenko, A. S.; Tanska, O. O. (Modern medical technology, 2019)
Purpose of the study. Study ST2 diagnostic marker in the development and severity of heart failure, evaluation of transplant status and the risk of developing a rejection crisis, as well as the risk of death in patients with cardiovascular disease. Material and methods. There were 41 patients under observation. The cases were conventionally divided into two groups: the first group of patients with chronic heart failure (n = 28), and the control group who performed orthotopic transplantation of the heart (n = 13). Results and discussion. These results suggest that ST2 is a real marker of chronic heart failure or a good predictor of mortality in decompensated patients. Changes in ST2 levels in patients after orthotopic cardiac transplantation may be potentially useful in detecting acute cellular rejection, as well as in controlling rejection therapy. The article is devoted to the analysis of the prognostic role of the ST2 biomarker in the pre and post-transplantation period. ST2 is one of the most promising diagnostic markers for the development and severity of heart failure, as well as the risk of death in patients with cardiovascular disease. ST2 is expressed in cardiomyocytes in response to pathological processes and various mechanical damage in the heart, which allows to diagnose cardiovascular diseases even before clinical manifestations. It is likely that ST2 level measurement of heart transplantation mayhave a diagnostic and prognostic value when evaluating the graft state and the risk of developing rejection. Conclusions. ST2 is one of the most promising diagnostic markers of development and severity of heart failure, as well as the risk of death in patients with cardiovascular disease. ST2 is expressed in cardiomyocytes inresponse to pathological processes and various mechanical damage in the heart, which allows to diagnose cardiovascular diseases even before clinical manifestations. Measuring the level of ST2 for heart transplantation may have a diagnostic and prognostic value in evaluating the condition of the graft and the risk of developing rejection.